Thermogravimetric analysis of banana peels via pyrolysis - Lim Wei Jie (2024)
Banana peels is outer covering of the banana fruit which rich in various organic matter. Banana peels as biomass waste that should disposal properly to reduce enviromental problems. It was potential become renewable energy such as bio-oil and biogas in pyrolysis. Unripe and ripe banana peel was used in pyrolysis. Study of characteristics biomass to determine the ability of biomass as a renewable energy source. Present research was conducted with thermogravimetric analysis to study the characteristic of ripe and unripe banana peel at different heating rates. The objectives of this research is investigate proximate and ultimate analysis of banana peel. Next, characterize banana peel by using SEM-EDX, FTIR, TGA and DSC for morphology structure, functional group and thermal stability of banana peels. Objectives also determine kinetic and thermodynamic of banana peel by using different isoconversional method via thermogravimetric analysis. TGA analyzer was used to analyze the weight loss of banana peel sample by increasing temperature over time with different heating rates of 10 °C/min, 20°C/min and 30°C/min. DSC method was run together within TG analysis to determine heat flow of sample as temperatre increase over time. Proximate analysis showed in content of volatile matter in banana peel, ultimate analysis showed elements hyrogen and oxygen were major elements. Averaged activation energy calculated from model-free isoconversional method Flynn-Wall-Ozawa(FWO), Friedman and Kissinger from 0.2-0.7 conversion were 48.82, 38.77 and 29.58 kJ/mol for unripe banana peel whereas 56.22, 59.86 and 31.55 kJ/mol for ripe banana peel. Pre-exponential factor obtained from FWO and Kissinger method was found to vary from 104 to 109 s-1. Thermodynamic analysis for enthalpy, Gibss free energy and entropy in average 40.29, 1750.61, and -5.54 kJ/mol for unripe banana peel. For ripe banana peel it showed average in 64.13, 1774.95 and -5.19 kJ/mol. Unripe banana peel more efficient in pyrolysis due to activation energy was lower than ripe banana peel. In short both types of banana peel was potential to become biorenewable energy source such as biochar and bio-oil. Banana peel possess good thermal stability and characteristics which capable high temperature and convert to bioenergy to produce heat and energy.